Accuracy and safety of C2 pedicle or pars screw placement: a systematic review and meta-analysis - Parisa Azimi; Taravat Yazdanian; Edward C. Benzel; Hossein Nayeb Aghaei; Shirzad Azhari; Sohrab Sadeghi; Ali Montazeri (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Study design Systematic review and meta-analysis. Aim The purpose of this study was to compare the safety and accuracy of the C2 pedicle versus C2 pars screws placement and free-hand technique versus navigation for upper cervical fusion patients. Methods Databases searched included PubMed, Scopus, Web of Science, and Cochrane Library to identify all papers published up to April 2020 that have evaluated C2 pedicle/pars screws placement accuracy. Two authors individually screened the literature according to the inclusion and exclusion criteria. The accuracy rates associated with C2 pedicle/pars were extracted. The pooled accuracy rate estimated was performed by the CMA software. A funnel plot based on accuracy rate estimate was used to evaluate publication bias. Results From 1123 potentially relevant studies, 142 full-text publications were screened. We analyzed data from 79 studies involving 4431 patients with 6026 C2 pedicle or pars screw placement. We used the Newcastle-Ottawa Scale (NOS) to evaluate the quality of studies included in this review. Overall, funnel plot and Begg’s test did not indicate obvious publication bias. The pooled analysis reveals that the accuracy rates were 93.8% for C2 pedicle screw free-hand, 93.7% for pars screw free-hand, 92.2% for navigated C2 pedicle screw, and 86.2% for navigated C2 pars screw (all, P value < 0.001). No statistically significant differences were observed between the accuracy of placement C2 pedicle versus C2 pars screws with the free-hand technique and the free-hand C2 pedicle group versus the navigated C2 pedicle group (all, P value > 0.05). Conclusion Overall, there was no difference in the safety and accuracy between the free-hand and navigated techniques. Further well-conducted studies with detailed stratification are needed to complement our findings.